Evaluation of Pre-harvest Microbiological Safety of Blueberry Production With or Without Manure-Derived Fertilizer - Shen, Xiaoye; Sheng, Lina; Benedict, Chris; Kruger, Chad E.; Su, Yuan; Schacht, Elizabeth; Zhang, Yifan; Zhu, Mei-Jun (Frontiers in Microbiology, 2020)
Blueberry is an important commodity in Washington State, which was one of the leading blueberry producers in the United States. As a ready-to-eat fruit, blueberry has no or limited post-harvest processing, highlighting an imperative need to evaluate its microbial safety during pre-harvest practice. This study accessed the microbiological safety of blueberry produced in a commercial blueberry field applied with or without manure-derived ammonium sulfate (AS) fertilizer in a 2-year study. Indicator microorganisms of total coliforms and generic E. coli, Shiga toxin-producing Escherichia coli (STEC), Salmonella, and Listeria monocytogenes were monitored in fertilizer, soil, foliar, and blueberry fruit samples by culture methods for each production season. The population of total coliforms in soils was 3.17–3.82 Log10 CFU/g, which was stable throughout the production season and similar between two cropping seasons. Generic E. coli in soils remained at very low levels throughout the 2018 production season. Total coliforms or generic E. coli was not detected in fertilizer, foliar, and blueberry fruit samples collected in both 2017 and 2018 production seasons. STEC and L. monocytogenes were below the detection limit in fertilizer, soil, foliar, and blueberry fruit samples collected in both production seasons. Salmonella was not detected except for soil samples collected pre- and post-fertilizer application in the 2018 cropping season. Collectively, data indicated, under good agricultural practices, blueberry fruits produced in the field with or without manure-derived AS fertilizers had no microbiological safety concern.